DESAIN PRODUK SISTEM MONITORING KUALITAS AIR KOLAM IKAN LELE BERBASIS SENSOR DAN MIKROKONTROLER - Separ Gunawan Sinaga; Abdul Waqi Adlan; Jeremia Tobing; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Water quality is a critical factor influencing the success of catfish farming, as parameters such as temperature, pH, and visual water conditions directly affect fish growth and survival. Conventional monitoring methods are generally performed manually, resulting in limited accuracy and delayed responses to environmental changes. This study aims to design and implement a real-time water quality monitoring system based on Arduino Uno integrated with multiple sensors, including DS18B20 for temperature, a pH sensor for acidity, TCS3200 for water color detection, and a water level sensor. The system was developed using a prototyping approach, involving hardware integration and software programming using Arduino IDE. Experimental testing was conducted using clean tap water and polluted river water containing algae to evaluate system performance. The results indicate that the system is capable of accurately detecting variations in water quality parameters. Temperature and pH readings successfully distinguished between optimal and non-optimal conditions, while the TCS3200 color sensor effectively identified changes in water color based on RGB values, providing more detailed information compared to conventional turbidity-based methods. The system also provides real-time visual output through an LCD and early warning alerts via LED and buzzer when water conditions exceed normal thresholds. The findings suggest that the proposed system offers a practical and effective solution for monitoring water quality in catfish farming, with potential implications for improving productivity and enabling more responsive environmental management.